Psychoeducation Analysis in Tafsir Al-Maraghi: An Integrated Approach - Zakiyah, Ermita (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
This research aims to look at the concept of psychoeducation according to Al-Maraghi's interpretation. Many phenomena in education are caused by a lack of harmony between academic achievement and student behavior, so psychoeducation is a solution to harmonize achievement and positive character with correct behavior patterns. Both following cultural and religious etiquette, this research method is library research with the perspective of Al-Maraghi's interpretation because it interpretation uses the methodology of manhaj al-adab al-ijtimai or social society so that Al-Maraghi's views on psychoeducation can be studied thoroughly. The data analysis in this research is by explaining verses from the Qur'an with Al-Maraghi's interpretation of psychoeducation and linking verses that prohibit bullying. The findings of this research are that the concept of psychoeducation explained by Al-Maraghi requires the role of all parties involved in the educational process so that education and psychology can be integrated and Allah becomes a person's benchmark in carrying out psychoeducation.